Fracture of a polyimide–elastimide posterior chamber intraocular lens following blunt orbital trauma. Issue 5 (September 2020) - Friehmann, Asaf; Sharon, Tal; Ophir, Shira Sheen; Assia, Ehud I
Purpose: Fracture of a three-piece polyimide–elastimide intraocular lens at the optic–haptic junction following blunt trauma is a possible complication after cataract surgery. We report a case of an isolated posterior chamber intraocular lens fracture caused by direct ocular blunt trauma. Case: A 51-year-old patient underwent blunt orbital trauma caused by a raw chicken egg that was thrown at him, as he was walking. The posterior chamber intraocular lens was found in the anterior chamber, with a broken optic–haptic junction. The intraocular lens was exchanged, followed by iris fixation and pupilloplasty, with satisfactory postoperative anatomical and optical outcomes. Discussion: The three-piece polyimide–elastimide intraocular lens was fractured at the optic–haptic junction. Although the fractured intraocular lens surface had a regular appearance, it has been previously reported that the polyimide haptic's durability is probably inferior to that of polymethylmethacrylate. Therefore, it is highly susceptible to shear stress induced by a blunt trauma. Conclusion: To our knowledge, this is an uncommon report of an implanted posterior chamber polyimide–elastimide intraocular lens fracture following blunt orbital trauma. Intraocular lens exchange and fixation had successful optical and anatomical results.